2018
DOI: 10.1111/imig.12463
|View full text |Cite
|
Sign up to set email alerts
|

Media Discussion on the Naturalization Policy for Syrians in Turkey

Abstract: This study focuses on the public opinion on the naturalization policy for Syrians in Turkey. It analyses news media coverage in the religious, far‐right newspaper (Yeni Akit), a centre‐right newspaper (Hürriyet), a social democrat newspaper (Cumhuriyet), and a socialist‐left news portal (Solportal). The research question is: What are the metaphors, arguments, and omissions produced by media of different ideologies about the possible citizenship of Syrians in Turkey? The results show that metaphors and argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Therefore, integration of Syrians into the host society stands out as a significant issue for Turkey. Şimşek () argues that the current “temporary” state may in fact discourage Syrians from wishing to integrate to host society, and Atasü‐Topçuoğlu () underlines that naturalization would give the rights of people under temporary protection a permanent nature. The AFAD survey from 2013 showed that five per cent of camp and eight per cent of non‐camp population stated that they did not wish to return to Syria; yet these proportion increased to 16 per cent overall in the 2017 AFAD survey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, integration of Syrians into the host society stands out as a significant issue for Turkey. Şimşek () argues that the current “temporary” state may in fact discourage Syrians from wishing to integrate to host society, and Atasü‐Topçuoğlu () underlines that naturalization would give the rights of people under temporary protection a permanent nature. The AFAD survey from 2013 showed that five per cent of camp and eight per cent of non‐camp population stated that they did not wish to return to Syria; yet these proportion increased to 16 per cent overall in the 2017 AFAD survey.…”
Section: Discussionmentioning
confidence: 99%
“…According to Şengül (), the director of the Turkish Red Crescent reported that they had received briefs from Prime Minister Erdogan that the term “guests” be used, and not “migrants” or “refugees”. Atasü‐Topçuoğlu () underlines that this word selection stemmed from the short‐term view of the problem. Seeing the crisis persisting, the Ministry of Interior declared a temporary protection regime in October 2011 that warranted non‐refoulement (Şimşek, ).…”
Section: Arrivals Of Syrians In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant theme in the domain of media representation is the politicization of the refugee issue. Atasü‐Topçuoğlu (2019) argues that the current political polarization in Turkey affects the public’s willingness to accept the presence of Syrians. Consequently, the metaphors and arguments used in Turkish newspapers differ according to ideological position.…”
Section: Syrians In Turkish Media: the State Of The Artmentioning
confidence: 99%
“… It is important to note that Atasü‐Topçuoğlu (2019) presents Hurriyet as a “centre‐right” newspaper. Here, we categorize Hürriyet before 2018 as “mainstream” in comparison with the other two major newspapers in Turkey, that is Sabah being pro‐government and Cumhuriyet being opposition.…”
mentioning
confidence: 99%